2017
DOI: 10.1371/journal.pone.0187648
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the characteristics and short-term prognosis of patients presenting with acute symptomatic pulmonary embolism

Abstract: BackgroundWe sought to examine sex-related differences in the characteristics and outcome in patients presenting with acute symptomatic pulmonary embolism (PE).MethodsWe conducted a retrospective cohort study of 2,096 patients diagnosed with acute PE. The characteristics were recorded at presentation. Treatment was at the discretion of patients’ physicians. The primary study outcome, all-cause mortality, and the secondary outcomes of PE-specific mortality, recurrent venous thromboembolism, and major bleeding w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
3
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 28 publications
3
40
3
11
Order By: Relevance
“…As consistently reported by other registries and cohort studies [11][12][13][14][15], in the present single-centre study, the proportion of females was higher (55.9%) and females were older compared to males although almost 60% of patients < 50 years were women. Risk factors and comorbidities showed real-world distribution with expected differences in males and females.…”
Section: Sex-specific Differences In Comorbidities and Initial Presensupporting
confidence: 88%
See 1 more Smart Citation
“…As consistently reported by other registries and cohort studies [11][12][13][14][15], in the present single-centre study, the proportion of females was higher (55.9%) and females were older compared to males although almost 60% of patients < 50 years were women. Risk factors and comorbidities showed real-world distribution with expected differences in males and females.…”
Section: Sex-specific Differences In Comorbidities and Initial Presensupporting
confidence: 88%
“…The nationwide inpatient sample of the United States of America (with > 276,000 patient discharge files) showed a higher incidence of PE in females compared to males [11]. In accordance, in most large registries females represented the majority of patients enrolled [12][13][14][15]. Most studies congruently reported that women were older at the PE event [11][12][13][14] and presented more frequently with dyspnoea while haemoptysis was more often observed in men [12,16].…”
Section: Introductionmentioning
confidence: 75%
“…16 This highlights the value of a comprehensive evaluation of patient comorbidities, which is absent from prior studies on this topic. 7,8 We also noted a difference in presenting symptoms between men and women. Women were more likely to present with dyspnea, whereas men were more likely to present with hemoptysis.…”
Section: Discussionmentioning
confidence: 69%
“…A multicenter study of greater than 7000 CTPA exams showed higher CT testing in females but higher positivity in men 22. When PE is present, women tend to have severe pulmonary disease with higher 30-day mortality and have higher risk of bleeding with anticoagulation 53 54. Our study did not evaluate the outcomes based on gender differences.…”
Section: Discussionmentioning
confidence: 78%
“…22 When PE is present, women tend to have severe pulmonary disease with higher 30-day mortality and have higher risk of bleeding with anticoagulation. 53 54 Our study did not evaluate the outcomes based on gender differences. While the gender differences in coronary artery disease are being extensively studied, attention should be paid to understand gender as a risk for PE on future studies.…”
Section: Discussionmentioning
confidence: 99%